Cover Image. (21st February 2023) - Xiong, Jianxue; Chen, Guoke; Yang, Yishi; Meng, Hailiang; Storozum, Michael; Allen, Edward; Wang, Hui; Wen, Shaoqing
Abstract : The cover image is based on the Research Article Mixed economy and dried foods: Dental indicators reveal Heishuiguo Han Dynasty population's environmental adaptation to the semi‐arid region of northwestern China by Jianxue Xiong et al., https://doi.org/10.1002/oa.3146 .